The Role of Islamic Psychology in Addressing Digital Anxiety Among Generation Z in the Era of Artificial Intelligence - Rifyal Novalia; Dinyah Rizki Yanti Zebua (EDUJAVARE: International Journal of Educational Research, 2026)
The rapid development of digital technology and artificial intelligence (AI) has transformed the lives of Generation Z while simultaneously creating new psychological challenges, including digital anxiety, social comparison, fear of missing out, information overload, technological uncertainty, and concerns regarding future academic and employment opportunities. This study aims to examine the role of Islamic Psychology in addressing digital anxiety among Generation Z in the era of artificial intelligence. The study employs a Systematic Literature Review (SLR) approach by examining relevant scholarly literature published in academic databases, including studies addressing Islamic Psychology, digital anxiety, Generation Z, artificial intelligence, spirituality, religious coping, and digital mental health. The selected literature was analyzed thematically to identify psychological challenges associated with digital transformation and Islamic psychological principles that may contribute to anxiety management. The findings indicate that Islamic Psychology provides a holistic framework for understanding digital anxiety through the integration of psychological, spiritual, moral, and existential dimensions. Concepts such as tawakkul, sabr, dhikr, muhasabah, shukr, and tazkiyat al-nafs can support emotional regulation, resilience, self-awareness, acceptance of uncertainty, and the development of meaningful relationships with technology. Islamic Psychology does not emphasize rejecting digital technology or AI but encourages balanced, ethical, critical, and purposeful engagement with technological environments. The study concludes that integrating Islamic psychological principles with contemporary psychological approaches can provide culturally relevant strategies for addressing digital anxiety among Muslim Generation Z and strengthening their psychological well-being, spiritual resilience, sense of identity, and ability to navigate the rapidly changing AI-driven environment.